STRATEGI DAKWAH GERAKAN KAMPUNG Al-QUR’AN DALAM MEMBENTUK MASYARAKAT QUR’ANI - M. Iqbal Nur Aulia Fazri; Tantan Hermansyah; Nasichah Nasichah (Universitas Pahlawan Tuanku Tambusai, 2023)
Abstract: College of Quran Sciences in 2018, around 65 percent of Indonesian people are still illiterate to the Koran, especially in rural areas or remote areas. Related to this data, the Al-Quran Village Movement is here to eradicate Al-Qur'an illiteracy. What makes the Al-Quran Village Movement special is the method by gathering volunteers from various campuses or universities, then these volunteers must pass tests according to the standardization that has been made, then these volunteers are distributed to areas that need Al-Quran education. So, with this look at the phenomena in the field using qualitative research methods with their approach. This research raises the formulation of the problem which is the focus of this research, namely how is the da'wah strategy of the Al-Qur'an Village Movement in forming a Qur'anic society? The theory in this study uses strategic management theory designed by Fred. R David. According to his assumptions, the strategy process uses three stages, namely, the strategy formulation stage, the strategy implementation stage and the strategy evaluation stage. From the results of the research that the author has analyzed, it can be concluded that the da'wah strategy for the formulation of the Al-Qur'an Village Movement is compiling a vision and mission, recruiting volunteers, determining the target villages. At the strategy implementation stage, several stages of initiation, regeneration and finalization were implemented. In the evaluation stage, the Al-Qur'an Village Movement reviewed the strategies that had been implemented by making reports in the form of diaries or diaries by the volunteers as well as photos and videos that had been determined by the committee. Keywords: Al-Qur'an, Al-Quran Village Movement, Da'wah strategy, Qur'anic society